2014
DOI: 10.3109/10717544.2014.935532
|View full text |Cite
|
Sign up to set email alerts
|

Permeation enhancer strategies in transdermal drug delivery

Abstract: Today, $74% of drugs are taken orally and are not found to be as effective as desired. To improve such characteristics, transdermal drug delivery was brought to existence. This delivery system is capable of transporting the drug or macromolecules painlessly through skin into the blood circulation at fixed rate. Topical administration of therapeutic agents offers many advantages over conventional oral and invasive techniques of drug delivery. Several important advantages of transdermal drug delivery are prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
219
0
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 407 publications
(252 citation statements)
references
References 76 publications
3
219
0
17
Order By: Relevance
“…As far as the drug release was concerned, the permeation enhancers or the penetration enhancers play important role of accelerating the drug release across the skin (when included in the transdermal delivery systems). Transdermal delivery of drugs can be enhanced through use of chemical enhancers, iontophoresis, electroporation, ultrasound, microneedles, jet injection and thermal poration (Marwah et al, 2014;Kumar and Philip, 2007). Out of these various methods of transdermal enhancement of drug permeation, the use of chemical enhancers has been reported to be the best method of increasing transport across the skin.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the drug release was concerned, the permeation enhancers or the penetration enhancers play important role of accelerating the drug release across the skin (when included in the transdermal delivery systems). Transdermal delivery of drugs can be enhanced through use of chemical enhancers, iontophoresis, electroporation, ultrasound, microneedles, jet injection and thermal poration (Marwah et al, 2014;Kumar and Philip, 2007). Out of these various methods of transdermal enhancement of drug permeation, the use of chemical enhancers has been reported to be the best method of increasing transport across the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Conjugating GA and chitosan results in a polymer for liver targeting with sustained release of drug through it (Marwah et al, 2014). Nanodelivery system helps in achieving high solubility (Modgill et al, 2014), intracellular uptake of drug (Morie et al, 2014) and show high stability (Kateb et al, 2011;Sharma et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Four renowned permeation enhancers such as oleic acid, n-methyl-2-pyrrolidone, propylene glycol and polyethylene glycol 400 were selected based on the literature. 23,26 The concentration of enhancers (5% w/w) was selected based on the literature wherein it was reported that these agents are safe for human use. 26 Figure 6 compares the permeation profile of dexamethasone in presence of different chemical agents aimed for improving the permeation.…”
Section: Resultsmentioning
confidence: 99%
“…23,26 The concentration of enhancers (5% w/w) was selected based on the literature wherein it was reported that these agents are safe for human use. 26 Figure 6 compares the permeation profile of dexamethasone in presence of different chemical agents aimed for improving the permeation. It can be seen that the permeation of dexamethasone was significantly (P<0.001) higher when along chain fatty acid (oleic acid) was incorporated, and the enhancement was ~2 folds higher than the control (formulation without enhancer).…”
Section: Resultsmentioning
confidence: 99%